Genistein, a Soybean Isoflavone, Promotes Wound Healing by Enhancing Endothelial Progenitor Cell Mobilization in Rats with Hemorrhagic Shock. Issue 4 (12th January 2023) - Peng, Xiaoyong; Zhu, Yu; Wu, Yue; Xiang, Xinming; Deng, Mengsheng; Liu, Liangming; Li, Tao; Yang, Guangming
Abstract: Severe trauma and hemorrhaging are often accompanied by delayed cutaneous wound healing. Soybean isoflavone is a natural phytoestrogen that has attracted great attention due to its protective effects against various injuries. Endothelial progenitor cells (EPCs) are precursor cells with directional differentiation characteristics. This study is to determine whether genistein (GEN), an isoflavone in soybean products, benefits wound healing in hemorrhagic shock (HS) rats by promoting EPC homing and to investigate the underlying mechanisms. In this study, it is found that GEN promotes skin wound healing in HS rats, which is due at least partly to the mobilization of endogenous EPCs to the injury site via angiotensin II (Ang‐II), stromal cell‐derived factor‐1alpha (SDF‐1α), and transforming growth factor beta(TGF‐ β) signaling. Abstract : Genistein (GEN) plays an important role in promoting skin wound healing after hemorrhagic shock (HS). The protective effects of GEN are associated with endogenous endothelial progenitor cells (EPCs) mobilization and homing to the injured site via Ang‐II, SDF‐1α, and TGF‐β signaling. More effort is warranted to investigate the underlying mechanisms of EPCs mobilization under shock states.